Impact of Previous Sternotomy on Outcome after Left Ventricular Assist Device Implantation - Zhigalov, Konstantin; Szczechowicz, Marcin; Mashhour, Ahmed; Mkalaluh, Sabreen; Isaev, Maxim; Kadyraliev, Bakitbek; Easo, Jerry; Ennker, Juergen; Eichstaedt, Harald; Weymann, Alexander (The Thoracic and Cardiovascular Surgeon, 2019)
Background The main purpose of this article is to investigate the impact of previous sternotomy (PS) on the outcome of three different left ventricular assist devices (LVAD).Methods Between June 2007 and February 2018, a total of 121 patients received HeartMate II (60.3%), HeartWare (12.4%), or HeartMate III (27.3%), with or without previous sternotomy (PS and non-PS groups, respectively). Propensity matching resulted in 44 patient pairs. The primary end point was overall survival at 30 days, 1 year, 2, and 5 years, postoperatively. Secondary end points were adverse events.Results The overall cumulative survival rates for the two study groups were significantly different (77, 63, 54, and 38% for non-PS group vs 64, 39, 27, and 24% for PS group, p = 0.036). In the PS group, there was a higher need for intraoperative implantation of short-term right ventricular assist device (22.7 vs 6.8%, p = 0.034) and a higher incidence of hepatic dysfunction (20.5 vs 4.5%, p = 0.025) and acute kidney dysfunction (40.9 vs 20.5%, p = 0.032).Conclusion PS is a reliable predictor of mortality and morbidity after LVAD implantation.
Keywords: left ventricular assist device; heart failure; previous sternotomy